INTEGER PROGRAMMING DENGAN PENDEKATAN METODE BRANCH AND BOUND UNTUK OPTIMASI SISA MATERIAL BESI (WASTE ) PADA PLAT LANTAI (STUDI KASUS : PASAR ELPABES BANJARSARI SURAKARTA) - Widi Hartono; Alfichri Dilian Yanuar Agus Putri; Sugiyarto Sugiyarto (Program Studi Teknik Sipil FT UNS, 2014)
Use of materials in the project implementation closely monitored both quality and quantity in accordance with the specifications and requirementsthat have been set. But the problem is, in the work field, material used by the workers can leave big piece of material waste. The aim of thisresearch is to know visible optimum to optimize iron cutting for reducing iron waste and knowing how big the differences of the amount of pieces ofiron in the work field and with Linear interger program. The location of the research is the construction of ELPABES market BanjarsariSurakarta in the year of 2013. The secondary data which is used is iron reinforcement data in the form of Bar Bending Schedule. The processingof the data using Branch and Bound Method and LINDO program. The secondary data which is used is iron reinforcement data in the form ofBar Bending Schedule. The processing of the data using Branch and Bound Method and LINDO.Program.Analysis result from Branch andBound Method can optimization waste in iron cut from floor plate which is iron with diameter 12 mm. total of cut residue 141,35 m with savingpercentage 1,5449% and iron with diameter 10 mm. total of cut residue 1208,3 m with saving percentage 4,0399%.